Oxytetracycline photodegradation by transition metals doped ZnO nanorods - Siavash Fathi; Bagher Aslibeiki; Reza Torkamani (Journal of Water and Environmental Nanotechnology)
In the recent decades, increasing of pollutant in water resources endanger the human life and other living things. Researchers have applied different methods to eliminate the water contaminants. Photocatalytic is one of these methods that have been used widely for wastewater treatment. In this study, a series of Mn, Fe, Co, Ni, and Cu doped ZnO nanorods were applied as visible-light-activated catalysts for oxytetracycline (OTC) degradation. Characterization of the nanorods was performed using XRD, FE-SEM, UV-Vis, and PL techniques. The results show that photocatalytic activity of the samples highly depends on morphology, size and band gap energy. The UV–Vis spectroscopy indicate that Fe doping has reduced the band gap energy to 2.91 eV. The variation of band gap permits absorption of low energy photons and excitation of valence band electrons. The photoluminescence spectra reveal that doping has an effective role in inhibiting the recombination of electron/hole pairs during photocatalytic process. The Mn-doped sample exhibits significantly increased photocatalytic activity and greater degradation rate constant (k) in comparison with the pure ZnO.